Energy‐Transfer Mechanisms in IrIII–EuIII Bimetallic Complexes. Issue 8 (26th June 2013) - Yu, Gang; Xing, Yadong; Chen, Fangfang; Han, Ruimin; Wang, Jianqiang; Bian, Zuqiang; Fu, Limin; Liu, Zhiwei; Ai, Xicheng; Zhang, Jianping; Huang, Chunhui
Abstract The bridging ligands in d–f bimetallic complexes play an important role in the excitation energy transfer (EET) process. To elaborate on the effect of the ligand on the EET process, a series of bridging ligands (μ‐L), 1‐(1′, 10′‐phenanthrolin‐2′‐yl)‐4, 4, 4‐trifluorobutane‐1, 3‐dione (phen3f), 1‐(1′, 10′‐phenanthrolin‐2′‐yl)‐4, 4, 5, 5, 5‐pentafluoropentane‐1, 3‐dione (phen5f), 1‐(2, 2′‐bipyridine‐6‐yl)‐4, 4, 4‐trifluorobutane‐1, 3‐dione (bpy3f), and 1‐(2, 2′‐bipyridine‐6‐yl)‐4, 4, 5, 5, 5‐pentafluoropentane‐1, 3‐dione (bpy5f), and their corresponding iridium complexes, [(dfppy)2Ir(μ‐L)] (dfppy=2‐(4′, 6′‐difluorophenyl)pyridinato‐N, C2′), as well as their corresponding heteroleptic IrIII–EuIII complexes [{(dfppy)2Ir(μ‐L)}3EuCl]Cl2 were synthesized and characterized. Photophysical and kinetic results revealed that the alternation of the bridge ligand resulted in a systemic difference in the lowest triplet‐state energy (T1) of the iridium complexes, the EET efficiency from iridium complexes to the EuIII ion, and a significant difference in the total luminescence quantum yields. Based on the nanosecond time‐resolved phosphorescence spectra, a model for the energy‐transfer mechanism was proposed for d–f bimetallic complexes, which indicated that the nonradiative relaxation of the excited energy of EuIII, especially energy dissipation by means of the T1 state, was the main reason for the discrepancy in the quantum yields of the four IrIII–EuIII complexes.